Implementasi Kebijakan Alokasi Dana Desa Program Bantuan Rumah Tidak Layak Huni di Nagari Pasar Bukit Air Haji Kecamatan Linggo Sari Baganti - Oktaviana, Rahmi; Malau, Hasbullah (Policy, Law and Political Research Center, 2023)
The purpose of this study was to examine the implementation of village fund allocation policies for the housing assistance program for uninhabitable housing in Nagari Pasar Bukit Air Haji, Linggo Sari Baganti sub-district, South Coastal District. This study uses a qualitative method of intrinsic case study type. Selection of informants is using purposive sampling method. Collecting data in this study is observation, interviews and documentation. The data analysis used is according to Miles and Huberman namely collection, reduction and presentation of data and drawing conclusions/verification. The results of the study are from 2019 to 2021 the uninhabitable housing assistance program has been carried out and is in accordance with the verified beneficiary criteria, it is proven that 18 different houses have been built and handed over to those entitled to receive assistance from the uninhabitable housing program. This has been proven by the fact that 18 houses that have been built for beneficiary communities are not suitable for habitation. This problem is very much in accordance with the theoretical analysis of Van Meter and Van Horn's policy implementation which includes regulations, usufructuary resources, financial resources, and the party responsible for the Policy.